2021
DOI: 10.1111/ddg.14374
|View full text |Cite
|
Sign up to set email alerts
|

Routine application of ex vivo confocal laser scanning microscopy with digital staining for examination of surgical margins in basal cell carcinomas

Abstract: Summary Background and objectives Ex vivo confocal laser scanning microscopy (CLSM) allows histologic examination of native tissue based on tissue reflection and nuclear fluorescence staining. The newly introduced digital staining process almost perfectly mimics conventional hematoxylin and eosin (HE) slides. The aim was to evaluate the new method in clinical routine, with regard to quality of findings and time requirements, in the examination of surgical margins of basal cell carcinomas. Patients and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 32 publications
0
11
1
Order By: Relevance
“…These studies have reported an overall sensitivity and specificity for detecting BCC of 73–96.6% and 89.2–99%, respectively, when compared to HE-stained paraffin or frozen sections. More recently, Grupp et al [8] used the same EVCM as us and achieved a sensitivity of 73.6% and a specificity of 96.5%, in surgical margins of 101 cases of BCC, when compared to HE paraffin sections. Most of these works involved ex vivo CM experts, with prior experience in CM interpretation [8, 22].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…These studies have reported an overall sensitivity and specificity for detecting BCC of 73–96.6% and 89.2–99%, respectively, when compared to HE-stained paraffin or frozen sections. More recently, Grupp et al [8] used the same EVCM as us and achieved a sensitivity of 73.6% and a specificity of 96.5%, in surgical margins of 101 cases of BCC, when compared to HE paraffin sections. Most of these works involved ex vivo CM experts, with prior experience in CM interpretation [8, 22].…”
Section: Discussionmentioning
confidence: 93%
“…More recently, Grupp et al [8] used the same EVCM as us and achieved a sensitivity of 73.6% and a specificity of 96.5%, in surgical margins of 101 cases of BCC, when compared to HE paraffin sections. Most of these works involved ex vivo CM experts, with prior experience in CM interpretation [8, 22]. In our study, the great similarity between the EVCM images and those obtained from HE-stained paraffin sections rendered their interpretation accessible to a pathologist novice in CM.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Analogous issues were observed in other studies conducted on digitally scanned conventional H&E stained BCC slides [ 63 ]. Similar false positive results also do occur during assessment of CLSM images by experienced dermatohistopathologists, as these structures are difficult to differentiate [ 72 ]. Therefore, this limitation is not confined to the algorithm itself and partly stem from the reduced contrast and image quality.…”
Section: Discussionmentioning
confidence: 91%
“…Most of the data are available for the diagnosis of basal cell carcinomas (BCC). In this case, a high specificity and sensitivity could be demonstrated in comparison to H&E diagnostics [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. An important application is particularly in the use of Mohs surgery.…”
Section: Introductionmentioning
confidence: 99%